Chemical Investigation of Some Capparis Species Growing in Egypt and their Antioxidant Activity. (2007) - Hamed, Ahmed R.; Abdel-Shafeek, Khaled A.; Abdel-Azim, Nahla S.; Ismail, Shams I.; Hammouda, Faiza M.
Abstract : Capparis cartilaginea and C. deserti growing in Egypt were investigated for their glucosiolates and rutin content. From Capparis cartilaginea four isothiocynates were isolated and identified using GC and EI/MS techniques. These compounds were butyl isothiocyanate (1), 6-methylsulphonylhexyl isothiocyanate (2), 7-methylsulphonylheptyl isothiocyanate (3) and 5-benzylsulphonyl-4-pentenyl isothiocyanate (4). In addition to compounds (1) and (2), two other compounds were isolated and identified from Capparis deserti . These compounds are 3-methylthiopropyl isothiocyanate (5) and [11-(2-butenylthio)6-undecenyl isothiocyanate] (6). Compounds (1), (2), (5) and (6) are reported in this study for the first time from Capparis deserti . The main flavonoid component in the studied species was isolated and identified as rutin by comparing the data with those reported. Also, quantitative evaluation of rutin in the two species was carried out by TLC-densitometric analysis. The antioxidant activity was done using diphenylpicrylhydrazyl (DPPH) radical scavenging method. The butanol fraction from C. cartilaginea and C. deserti showed the highest antioxidant properties.